2019
DOI: 10.3390/safety5030054
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Fitness and Marksmanship in Police Officers

Abstract: Police officers may be required to discharge their weapon under physical duress. The purpose of this study was to investigate the relationship between fitness and marksmanship to facilitate future strategies to improve marksmanship. Retrospective data were provided for thirty-four police officers (mean age = 40.48 ± 6.66 years: mean weight = 100.60 ± 19.82 kg: mean height = 180.42 ± 6.87 cm) from a US-based law enforcement agency. Data included four different fitness measures and three different shooting scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Furthermore, the significant correlations (p < .0001) between grip strength and marksmanship performance were better in the non-dominant hand (left hand: r = .475) than the dominant hand (right hand: r = .398). Conversely, Muirhead et al (2019) found that while grip strength was significantly correlated to marksmanship scores in a dynamic shooting scenario (r = -.367, p < .05), it did not correlate to the other marksmanship shooting events (static shoot, r = -.001; positive identification shoot, r = 0.040). Muirhead et al (2019) detailed a potential explanation for the conflicting results between studies in that there were no correlations between the different shooting scenarios.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, the significant correlations (p < .0001) between grip strength and marksmanship performance were better in the non-dominant hand (left hand: r = .475) than the dominant hand (right hand: r = .398). Conversely, Muirhead et al (2019) found that while grip strength was significantly correlated to marksmanship scores in a dynamic shooting scenario (r = -.367, p < .05), it did not correlate to the other marksmanship shooting events (static shoot, r = -.001; positive identification shoot, r = 0.040). Muirhead et al (2019) detailed a potential explanation for the conflicting results between studies in that there were no correlations between the different shooting scenarios.…”
Section: Introductionmentioning
confidence: 82%
“…Conversely, Muirhead et al (2019) found that while grip strength was significantly correlated to marksmanship scores in a dynamic shooting scenario (r = -.367, p < .05), it did not correlate to the other marksmanship shooting events (static shoot, r = -.001; positive identification shoot, r = 0.040). Muirhead et al (2019) detailed a potential explanation for the conflicting results between studies in that there were no correlations between the different shooting scenarios. In addition to static and dynamic shooting scenarios, research has shown that increases in distance can negatively impact accuracy and variance (Dopsaj et al, 2020;Dopsaj et al, 2019).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…As such, grip endurance may be a more important factor. Furthermore, research by Muirhead et al [28] has shown that grip strength can range from negatively (r = −0.367) to positively (r = 0.040) correlating with police officer marksmanship task (aim was the highest possible score) depending on the nature of the shooting task. As such, the nature of the marksmanship component in the OPSA may have influenced the grip strength requirement to align and hold a sight picture on the target with their weapon and, as correct sight pictures were a requirement before progressing in the OPSA, may have influenced outcome times.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute strength as measured by an isometric leg/back dynamometer (LBDa) was found to not differentiate between high and low performers in a group of officers performing an occupationally specific physical agility test (PAT) [11]. In contrast, Muirhead et al (2019) reported that LBDa scores were associated with a positive identification shooting scenario (r = 0.344, P < 0.05) and the officers' total score across the three marksmanship scenarios (i.e., static marksmanship, move and shoot, positive identification) performed in this study (r = 0.350, P < 0.05). Based on these findings, it is evident that the relationships between relative strength by an isometric leg/back dynamometer (LBDr) and an lower body power among law enforcement officers of varying strength levels has not been fully explored.…”
Section: Introductionmentioning
confidence: 98%